Business Intelligence Applied to Sentiment Analysis in a Higher Education Institution - Varela, Bruno dos Santos (My University, 2021)
Social media allows institutions to not only publicize their work and get feedback from the community about it, but also to keep in touch with their alumni network and foster conversations between the academic community. While sentiment analysis allows a better understanding of what is being said about a brand and how to improve the use of this communication platform. The main goal of the current work is to build a Business Intelligence System for a Higher Education Institution (HEI) based on content extracted from social media. So, Posts, likes, dislikes, shares, comments and number of visits were extracted from Facebook, Google Maps Reviews, Instagram, LinkedIn, Student Forums, Twitter and YouTube. With this data and the ETL process a Data Warehouse (DW) in SQL Server and 17 Dashboards in Power BI were developed. Posts that had the most likes were about reporting a death of someone from the school, the school mascot, the pandemic or welcoming new students. Overall, the weekends were the days with more interactions. Students are concerned about accommodation, transport, and the school academic offer. This analysis allows a better understanding of what is being said about this HEI and how to improve the communication strategy
Keywords: Business intelligence; Sentiment analyses; Social media; Digital marketing; Text mining; Higher education institutions; Information behaviour; Social data